Estudio de Mobbing en una Institución de Educación Superior en Hidalgo (2019)
The objective of this research is to conduct a study to determine the degree of bullying perceived or perceived in the teaching staff of a public institution of higher education (IES), located in the central part of the state of Hidalgo, based on the theoretical position and conceptual of Leymann. This research considers the conceptualization of the mobbing phenomenon, from its antecedents, concepts and studies in the organizational context. The instrument that allows the measurement of mobbing, supported with validity and reliability, is the questionnaire called LIPT-60 ("Leymann Inventory of Psychological Terrorization"). The results obtained describe the existence of mobbing in the institution of higher education, with values observed below level 1, specifically in the subscales of job loss, incommunication, and overt intimidation. That is why in higher education institutions is essential to perform this type of work in order to identify, assess and know if there are risks of workplace harassment, to be in possibility if this were the case to have timely preventive measures. In this context, analyzing the results will establish prevention strategies to reduce or eradicate workplace harassment in this organization.